2019
DOI: 10.1039/c9ra05491j
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing oxygen and hydrogen evolution activities of perovskite oxide LaCoO3via effective doping of platinum

Abstract: Among the perovskite LaCo1−xPtxO3−δ catalysts, LaCo0.94Pt0.06O3−δ proved best for catalyzing OER/HER, with η = 454/294 mV, which might be attributed to LCP6 having the eg orbital filling of Co closest to 1.2.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(22 citation statements)
references
References 44 publications
1
21
0
Order By: Relevance
“…This performance was compared with those of recently reported oxide-based EWS systems (Figure 7d). [78,85,87,91,92,94,96,[102][103][104][105] The obtained results confirmed that CMO-U@CC exhibited improved electrocatalytic activity with faster kinetics and good stability.…”
Section: Aqueous Rechargeable Zinc-air Battery-driven Electrochemical Water Splittingsupporting
confidence: 64%
“…This performance was compared with those of recently reported oxide-based EWS systems (Figure 7d). [78,85,87,91,92,94,96,[102][103][104][105] The obtained results confirmed that CMO-U@CC exhibited improved electrocatalytic activity with faster kinetics and good stability.…”
Section: Aqueous Rechargeable Zinc-air Battery-driven Electrochemical Water Splittingsupporting
confidence: 64%
“…It is found that the Co 3+ /Co 2+ ratio of LSCFO (1.50) is larger than those of LCO (0.84), LCFO (1.11), and LSCO (0.90). Previous studies showed that the ratio of Co 3+ to Co 2+ can act as the descriptor of the catalytic activity toward OER. ,, The larger ratio of Co 3+ to Co 2+ implies the better catalytic activity toward OER. Therefore, LSCFO is believed to exhibit the superior catalytic activity toward OER.…”
Section: Resultsmentioning
confidence: 99%
“…Conversely, if the e g orbital occupation is less than 1, the strong bonding between the catalyst and the adsorbate can poison the catalyst by hindering the desorption process and reducing the number of available binding sites. A correlation between activity and e g orbital filling has been suggested for some HER catalysts as well. , However, in many cases, assignment of the e g orbital occupancy has been done by electron count and based on the assumption of a certain spin state. ,,,, …”
Section: Resultsmentioning
confidence: 99%
“…A correlation between activity and e g orbital filling has been suggested for some HER catalysts as well. 76,77 However, in many cases, assignment of the e g orbital occupancy has been done by electron count and based on the assumption of a certain spin state. 1,13,73,76,77 We used DFT calculations to investigate the electronic structure and identify descriptors that led to the enhanced electrocatalytic activity of CaSrFe 0.75 Co 0.75 Mn 0.5 O 6−δ (CSFCM).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation